Ultimate cruise ship building freedom of the seas - Peterson, Alan; Fox, Michael R.; Landin, Bo
This documentary is about the structures of the Ship. A cruise ship bigger than the Queen Mary II? Sounds impossible. But at a quarter mile long and 18 stories high, weighing in at 160,000 tons, Royal Caribbean's new Freedom of the Seas became the largest passenger ship in the world when she launched in June. The Discovery Channel special will take you behind the scenes to showcase the process of building the world's largest ocean liner.